Longitudinal follow up of coiled intracranial aneurysms: the impact of contrast enhanced MRA in comparison to 3DTOF MRA at 3T. Issue 1 (December 2015) - Anzalone, Nicoletta; De Filippis, C.; Scomazzoni, F.; Calori, G.; Iadanza, A.; Simionato, F.; Righi, C.
Abstract Background The role of 3DTOF MRA in the follow up (FU) of coiled cerebral aneurysms is well established. Though CEMRA (Contrast Enhanced Magnetic Resonance Angiography) has demonstrated to be superior to 3DTOF MRA in showing aneurysms residual patency, its role is still debated. The aim of this study was to verify if there is an added value of CEMRA in the long term follow up of coiled treated aneurysms. Methods Sixty-four cerebral aneurysms treated with GDC coils regularly followed up with 3DTOF and CEMRA at 3T every year for at least four years were included in the study. Both MR exams were evaluated and scored according to Montreal scale. Residual patency rates and modifications during follow up as depicted by the two techniques on the three item score of the Montreal scale (TO = total occlusion, NR = neck remnant and AR = aneurysm remnant) were registered along with management decisions. Intertechnique agreement was evaluated with respect to patency scoring in earlier and later stages of FU. Moreover the predictive value of earlier scores for both acquisitions with respect to management decision was assessed. Results At 1 year FU, TO to NR to AR score ratios were 31/23/10 and 22/31/11 for 3DTOF and CEMRA respectively, whereas at 4 years FU they evolved to 28/22/14 and 19/28/17 respectively. Fifteen patencies (all AR) out of 64 aneurysms were judged suitable of retreatment evaluation during FU and 8 retreatments were effectively performed after overall benefit/risk ratio considerations. All 15 reopenings were equally depicted by both techniques except one that was depicted earlier on CEMRA. Among the 9 TO at TOF MRA and NR at CEMRA at 1 year, 3 cases enlarged to NR at TOF at 4 years, most remained stable. Among the 22 cases judged NR at 1 years with both techniques, 3 cases showed enlargement at both techniques, while in other 3 cases AR was evident only at 3DCEMRA and they were not retreated. Conclusions CEMRA superiority in depiction of intracranial aneurysms recanalization is confirmed by our data. Nevertheless a clear impact in patient management is apparently not evident. Evidence of occlusion at 3DTOF FU may not need the addition of a CEMRA study.